Discrete melanocortin sensitive neuroanatomical pathway linking the ventral premmamillary nucleus to the paraventricular hypothalamus - Gautron, Laurent (2013)
The physiological effects of melanocortin-4 receptor (MC4-R) on metabolism have been hypothesized to be mediated individually or collectively by neuronal groups innervating the paraventricular nucleus of the hypothalamus (PVH). The present study was designed to identify MC4-R-expressing neurons that innervate the PVH using retrograde tract tracing techniques in the MC4-R-GFP reporter mice. Our initial mapping identified very limited projections from MC4-R-expressing neurons to the PVH. This included a defined population of MC4-R-positive neurons located in the ventral premmamillary nucleus (PMv). Anterograde tracing experiments confirmed projections from PMv neurons to the medial parvicellular subdivision of the PVH, in close proximity to oxytocin neurons and β-endorphin-containing fibers. Given the known stimulatory effects of leptin and sexual odorants exposure on many PMv neurons, it was expected that MC4-R-expressing neurons in the PMv might be responsive to leptin and activated by odors exposure. Contrary to expectation, MC4-R-GFP neurons in the PMv do not respond to leptin as demonstrated by double labeling for GFP and leptin-induced phosphorylated STAT3. However, we found that Fos expression is induced in large subset of MC4-R-GFP neurons in the PMv in response to opposite sex odors. Collectively, these results provide evidence for a previous unrecognized role of MC4-R expressed by neurons innervating the PVH that are also sensitive to reproductive cues.